PDMAPAA-coated TA-APTES-coated PVDF composite hydrogel film and preparation method and application thereof
By forming a TA-APTES micro-nanosphere coating on the PVDF base film, and using Fe3+ and TA to construct a dual autocatalytic system to catalyze DMAPAA polymerization, PDMAPAA@TA-APTES@PVDF composite hydrogel film was prepared, which solved the problems of membrane pollution and preparation process in traditional membrane separation technology, and achieved high-throughput and anti-pollution performance membrane preparation.
Patent Information
- Application Number
- CN202411988035.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Traditional membrane separation technology reduces flux due to membrane pollution when treating oily wastewater, low separation efficiency and high energy consumption. The preparation process of traditional composite hydrogel films is complicated and the conditions are harsh, making it difficult to prepare without external stimulation at room temperature or low temperature.
A TA-APTES micro-nanosphere coating was formed on the PVDF base film by Michael addition reaction of TA and APTES, and a dual autocatalytic system was constructed using Fe3+ and TA to catalyze the polymerization of DMAPAA on the membrane surface, and a PDMAPAA@TA-APTES@PVDF composite hydrogel film was prepared.
It realizes the rapid, efficient and large-scale preparation of high-throughput anti-pollution composite hydrogel film under mild conditions, improves the flux and anti-pollution performance of the film, and can operate stably under high concentration oil-water separation conditions for a long time.
Smart Images

Figure CN119708592A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a PDMAPAA@TA-APTES@PVDF composite hydrogel membrane, and belongs to the technical field of preparation of environmental functional materials. Background Art
[0002] Oily wastewater generated in industry and daily life has a serious impact on ecosystems and human health. The efficient treatment of oily wastewater is an urgent concern worldwide. Membrane separation technology stands out from other traditional methods due to its advantages such as energy saving, mild operating conditions and high cost-effectiveness. However, membrane fouling inevitably causes a serious decline in the flux of traditional membranes. This fatal weakness not only leads to low separation efficiency and high energy consumption, but also restricts the development of this technology in oily wastewater treatment. Therefore, it is very important to improve the anti-fouling performance of separation membranes.
[0003] Surface hydrophilic modification is an effective way to enhance the antifouling performance of membranes. It can prevent oil and other pollutants from directly contacting and adhering to the membrane surface by forming a hydration layer and micro-nanostructure on the membrane surface, forming an effective "pollution resistance" barrier and reducing the pollution of oil on the separation membrane. Therefore, the stronger the hydration of the membrane material, the stronger its oil pollution resistance. Hydrogel is a polymer material with a three-dimensional network structure formed by cross-linking hydrophilic compounds through chemical and physical effects. It has ultra-high hydrophilicity and can form a solid hydration layer on the membrane surface. In addition, the low Young's modulus of hydrogel gives the membrane surface a large exclusion volume and enhances the steric hindrance effect. Therefore, the hydrogel layer of the hydrogel membrane will integrate and strengthen the pollution resistance mechanism on the membrane surface, improve the hydrophilicity and oleophobicity of the membrane surface, and thus improve the permeability and anti-pollution performance of the membrane surface. However, the traditional process of preparing composite hydrogel membranes is relatively complicated and the reaction conditions are relatively harsh. The polymerization process usually includes monomers, chemical crosslinkers and toxic additives. The gelation process depends on external stimulation and requires strong ultraviolet irradiation or high heating temperature. Therefore, the preparation of composite hydrogel films at room temperature or low temperature without external stimulation remains a major challenge.
[0004] In recent years, the construction of a polyphenol-metal ion autocatalytic system based on the catalytic properties of mussel-like / natural polyphenols and the combination of transition metals has become an important research hotspot for the construction of super-strong hydrogels based on mussel-like / natural polyphenols. The new dual autocatalytic system composed of a variety of variable-valence metal ions and compounds containing catechol groups can effectively catalyze the polymerization of hydrogels without external stimulation and prepare hydrogels efficiently and quickly. However, the application of this method to prepare hydrogel films has not been reported. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to overcome the technical defects of the prior art and provide a method for preparing PDMAPAA@TA-APTES@PVDF composite hydrogel membrane in an efficient, rapid and large-scale manner. Specifically, the present invention first uses the Michael addition reaction of TA and APTES to form a TA-APTES micro-nanosphere coating on a PVDF base membrane to obtain a TA-APTES@PVDF membrane, and then uses an oxidative high-valent metal iron ion (Fe 3+ ) and reducing tannic acid (TA) containing catechol functional groups initiated the polymerization of dimethylaminopropylacrylamide (DMAPAA) on the surface of TA-APTES@PVDF membrane to prepare a high-throughput anti-fouling PDMAPAA@TA-APTES@PVDF composite hydrogel membrane.
[0006] The present invention modifies the surface of commercial PVDF membrane, which is simple to operate, has a short modification reaction time, high efficiency, is suitable for roll film production lines, and is suitable for industrial production. The prepared anti-pollution oil-water separation membrane has a super-hydrophilic surface and excellent anti-pollution properties, and can operate stably for a long time under high-concentration oil-water separation conditions.
[0007] The present invention modifies the TA-APTES micro-nanosphere coating on the PVDF base film, and then applies oxidative high-valent metal iron ions (Fe 3+ ) and tannic acid (TA) composed of a dual autocatalytic system, which triggered the polymerization of dimethylaminopropyl acrylamide (DMAPAA) on the membrane surface, and quickly and efficiently prepared a high-throughput and anti-fouling PDMAPAA@TA-APTES@PVDF composite hydrogel membrane under mild conditions, which improved the flux and anti-fouling performance of the membrane, solved the problems of traditional separation membrane pollution, low flux and poor interface binding stability, and enabled the prepared PDMAPAA@TA-APTES@PVDF composite hydrogel membrane to separate a variety of oil-water emulsions, with greatly improved separation efficiency and anti-fouling performance, and able to operate stably for a long time under high-concentration oil-water separation conditions.
[0008] The technical solution adopted by the present invention is as follows. The present invention is completed by three steps of reaction:
[0009] (1) Preparation of PVDF base membrane: A commercially available hydrophobic PVDF membrane (polyvinylidene fluoride membrane) was completely infiltrated with anhydrous ethanol to obtain a PVDF base membrane.
[0010] (2) Synthesis of TA-APTES@PVDF membrane: TA-APTES@PVDF membrane was prepared by forming a TA-APTES micro-nanosphere coating on the PVDF base membrane using the Michael addition reaction of TA and APTES.
[0011] (3) Synthesis of PDMAPAA@TA-APTES@PVDF composite hydrogel membrane: The prepared TA-APTES@PVDF membrane was placed in a 3+ , MBAA, (NH4)2S2O8 and DMAPAA mixed solution in a beaker, Fe 3+ A dual autocatalytic system was constructed with TA to catalyze the polymerization of DMAPAA to obtain PDMAPAA@TA-APTES@PVDF composite hydrogel membrane.
[0012] Wherein, in step (1), the PVDF membrane can be subjected to the next step of reaction after being soaked in anhydrous ethanol.
[0013] Wherein, in step (2), the solvent used is 25-35 ml of deionized water; the TA used is 40-60 mg, and the APTES used is 600-800 μl; the reaction conditions are 25° C. water bath shaking for 30-50 min.
[0014] Wherein, in step (3), the solvent used is 4-8 ml of deionized water; the FeCl3·6H2O used is 50-70 mg, (NH4)2S2O8 is 8-12 mg, and MBAA is 10-14 mg. After they are completely dissolved, 30-70 μl of DMAPAA is added; the reaction conditions are 1.5-2.5 h under 25°C water bath shaking conditions.
[0015] The above PDMAPAA@TA-APTES@PVDF composite hydrogel membrane was applied to oil-water separation experiments:
[0016] The volume ratio of water to oil in the oil-water emulsion used in this experiment was 99:1, and 10 mg of ionic surfactant was added. Stirring for 12 hours formed a stable emulsion, and the oil-water emulsion was separated by a suction filtration device at a pressure of 0.2 bar and a stirring speed of 300 r / min. The transmittance between wavelengths of 400nm and 800nm was measured using an ultraviolet spectrophotometer (UH5300 model) to calculate the oil concentration in the emulsion and filtrate. The separation efficiency is calculated by the following formula:
[0017]
[0018] Where S is the separation efficiency of the oil-in-water emulsion, T feed is the average permeability of the prepared emulsion. T0 is the average permeability of the corresponding pure water; T1 is the average permeability of the filtrate after separation.
[0019] The formula for calculating the membrane permeation flux is as follows:
[0020]
[0021] Where J is the permeation flux of the membrane (L·m-2 ·h -1 bar -1 ), A is the effective area of the separation membrane (m 2 ), Δt is the time taken for the solution to pass through the membrane (h), and ΔP is the operating pressure (bar).
[0022] exist Figure 6 The separation substances involved are petroleum ether, hexane, cyclohexane, dichloroethane and toluene, and the emulsion to be separated refers to an emulsion in which the volume ratio of water to oil (the above substances) is 99:1.
[0023] The beneficial effects of the present invention are:
[0024] (1) The present invention uses PVDF as the base film, which has low material price, good mechanical properties, is environmentally friendly, and has good recycling performance.
[0025] (2) Use iron ions (Fe 3+ ) and tannic acid (TA) to construct a dual autocatalytic system to quickly, efficiently and large-scale prepare PDMAPAA@TA-APTES@PVDF composite hydrogel membrane under mild conditions.
[0026] (3) The prepared PDMAPAA@TA-APTES@PVDF composite hydrogel membrane has high flux, superhydrophilicity, underwater superoleophobicity and long-term stable anti-fouling properties.
[0027] (4) The preparation method of the present invention is simple, easy to operate, has low energy consumption, is easy to handle, and has no secondary pollution. It conforms to the concept of green chemistry and has good application prospects in the field of oil-water separation. The prepared anti-pollution oil-water separation membrane has super hydrophilic properties and excellent anti-pollution properties, can operate stably for a long time, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron micrograph of the hydrophobic PVDF base membrane.
[0029] Figure 2 This is the scanning electron microscopy image of the prepared TA-APTES@PVDF membrane.
[0030] Figure 3 Scanning electron microscopy image of the prepared PDMAPAA@TA-APTES@PVDF composite hydrogel membrane
[0031] Figure 4 This is a photo of the water contact angle of the prepared PDMAPAA@TA-APTES@PVDF composite hydrogel film.
[0032] Figure 5 This is the underwater dichloroethane contact angle photo of the prepared PDMAPAA@TA-APTES@PVDF composite hydrogel film.
[0033] Figure 6 The permeation flux and separation efficiency of the prepared PDMAPAA@TA-APTES@PVDF composite hydrogel membrane (a) and after treatment in acid (b), alkali (c), and salt (d) environments for different types of oil-water emulsions.
[0034] Figure 7 This is a diagram of the cyclic separation experiment of the prepared PDMAPAA@TA-APTES@PVDF composite hydrogel membrane.
[0035] Figure 8 This is the mass preparation of PDMAPAA@TA-APTES@PVDF composite hydrogel membrane and its permeation flux and separation efficiency for n-hexane emulsion.
[0036] Specific example method
[0037] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and provides a detailed operation process and specific reaction conditions, but the protection scope of the present invention is not limited to the following embodiments.
[0038] Example 1
[0039] Step 1: Preparation of PVDF base membrane: A commercially available hydrophobic PVDF membrane is completely infiltrated with anhydrous ethanol to obtain a PVDF base membrane.
[0040] Figure 1 It can be seen that the surface of the hydrophobic PVDF base membrane is relatively smooth and the pore size is sparse.
[0041] Step 2: Synthesis of TA-APTES@PVDF membrane: Dissolve 50 mg TA (tannic acid) in a beaker containing 25 ml deionized water, add 600 μl APTES (3-aminopropyltriethoxysilane), and when APTES begins to hydrolyze, place the PVDF base membrane soaked in anhydrous ethanol into it, seal the beaker with a sealing film, and shake in a water bath at 25°C for 40 minutes. TA and APTES undergo Michael addition reaction to form a TA-APTES micro-nanosphere coating on the PVDF base membrane to prepare a TA-APTES@PVDF membrane.
[0042] Figure 2 It can be seen that compared with the PVDF base membrane, the surface of the TA-APTES@PVDF membrane has grown many small balls, becomes rough, and the pore size is reduced, indicating that TA-APTES is successfully cross-linked on the surface of the PVDF membrane.
[0043] Step 3: Synthesis of PDMAPAA@TA-APTES@PVDF composite hydrogel membrane: 58 mg FeCl3·6H2O, 10 mg (NH4)2S2O8, and 12 mg MBAA (N,N-methylenebisacrylamide) were dissolved in a beaker containing 6 ml of deionized water, 50 μl DMAPAA (dimethylaminopropyl acrylamide) was added, and the prepared TA-APTES@PVDF membrane was placed in it. The beaker was sealed with a sealing film and shaken in a water bath at 25 °C for 2 h. 3+ A dual autocatalytic system was constructed with TA to catalyze the polymerization of DMAPAA to obtain PDMAPAA@TA-APTES@PVDF composite hydrogel membrane.
[0044] Figure 3 It can be seen that compared with the TA-APTES@PVDF membrane, a gel structure grows on the surface of the PDMAPAA@TA-APTES@PVDF composite hydrogel membrane, which wraps the small balls and has a smaller pore size, indicating that DMAPAA is successfully polymerized on the surface of the TA-APTES@PVDF membrane.
[0045] Figure 4 It can be seen that the PDMAPAA@TA-APTES@PVDF composite hydrogel membrane exhibits superhydrophilic properties.
[0046] Figure 5 It can be seen that the PDMAPAA@TA-APTES@PVDF composite hydrogel film has underwater superoleophobic properties.
[0047] Figure 6 It can be seen that after the PDMAPAA@TA-APTES@PVDF composite hydrogel membrane was treated in acid, alkali and salt environments, the permeation flux and separation efficiency of different types of oil-water emulsions did not change.
[0048] Figure 7 It can be seen that the PDMAPAA@TA-APTES@PVDF composite hydrogel membrane still has a high permeation flux and separation efficiency for n-hexane emulsion after 15 cycles of separation.
[0049] Figure 8 It can be seen that the large-scale prepared PDMAPAA@TA-APTES@PVDF composite hydrogel membrane has high permeation flux and separation efficiency.
[0050] Embodiment 2:
[0051] Step 1: Preparation of PVDF base membrane: A commercially available hydrophobic PVDF membrane is completely infiltrated with anhydrous ethanol to obtain a PVDF base membrane.
[0052] Step 2: Synthesis of TA-APTES@PVDF membrane: Dissolve 50 mg TA in a beaker containing 25 ml deionized water, add 600 μl APTES, and when APTES begins to hydrolyze, place the PVDF base membrane soaked in anhydrous ethanol into it, seal the beaker with a sealing film, and shake in a water bath at 25°C for 40 minutes. TA and APTES undergo Michael addition reaction to form a TA-APTES micro-nanosphere coating on the PVDF base membrane to prepare a TA-APTES@PVDF membrane.
[0053] Step 3: Synthesis of PDMAPAA@TA-APTES@PVDF composite hydrogel membrane: 58 mg FeCl3·6H2O, 10 mg (NH4)2S2O8, and 12 mg MBAA were dissolved in a beaker containing 6 ml deionized water, 50 μl DMAPAA was added, and the prepared TA-APTES@PVDF membrane was placed in it. The beaker was sealed with a sealing film and shaken in a water bath at 25 °C for 2 h. 3+ A dual autocatalytic system was constructed with TA to catalyze the polymerization of DMAPAA to obtain PDMAPAA@TA-APTES@PVDF composite hydrogel membrane.
[0054] Embodiment 3:
[0055] Step 1: Preparation of PVDF base membrane: A commercially available hydrophobic PVDF membrane is completely infiltrated with anhydrous ethanol to obtain a PVDF base membrane.
[0056] Step 2: Synthesis of TA-APTES@PVDF membrane: Dissolve 50 mg TA in a beaker containing 25 ml deionized water, add 700 μl APTES, and when APTES begins to hydrolyze, place the PVDF base membrane soaked in anhydrous ethanol into it, seal the beaker with a sealing film, and shake in a water bath at 25°C for 50 minutes. TA and APTES undergo Michael addition reaction to form a TA-APTES micro-nanosphere coating on the PVDF base membrane to prepare a TA-APTES@PVDF membrane.
[0057] Step 3: Synthesis of PDMAPAA@TA-APTES@PVDF composite hydrogel membrane: 58 mg FeCl3·6H2O, 10 mg (NH4)2S2O8, and 12 mg MBAA were dissolved in a beaker containing 6 ml deionized water, 50 μl DMAPAA was added, and the prepared TA-APTES@PVDF membrane was placed in it. The beaker was sealed with a sealing film and shaken in a water bath at 25 °C for 2 h. 3+ A dual autocatalytic system was constructed with TA to catalyze the polymerization of DMAPAA to obtain PDMAPAA@TA-APTES@PVDF composite hydrogel membrane.
[0058] Embodiment 4:
[0059] Step 1: Preparation of PVDF base membrane: A commercially available hydrophobic PVDF membrane is completely infiltrated with anhydrous ethanol to obtain a PVDF base membrane.
[0060] Step 2: Synthesis of TA-APTES@PVDF membrane: dissolve 50 mg TA in a beaker containing 25 ml deionized water, add 700 μl APTES, and when APTES begins to hydrolyze, place the PVDF base membrane soaked in anhydrous ethanol into it, seal the beaker with a sealing film, and shake in a water bath at 25°C for 40 minutes. TA and APTES undergo Michael addition reaction to form a TA-APTES micro-nanosphere coating on the PVDF base membrane to prepare a TA-APTES@PVDF membrane.
[0061] Step 3: Synthesis of PDMAPAA@TA-APTES@PVDF composite hydrogel membrane: 58 mg FeCl3·6H2O, 10 mg (NH4)2S2O8, and 12 mg MBAA were dissolved in a beaker containing 6 ml deionized water, 70 μl DMAPAA was added, and the prepared TA-APTES@PVDF membrane was placed in it. The beaker was sealed with a sealing film and shaken in a water bath at 25 °C for 2 h. 3+ A dual autocatalytic system was constructed with TA to catalyze the polymerization of DMAPAA to obtain PDMAPAA@TA-APTES@PVDF composite hydrogel membrane.
[0062] Embodiment 5:
[0063] Step 1, preparation of PVDF base membrane: completely infiltrate a commercially available hydrophobic PVDF membrane with anhydrous ethanol to obtain a PVDF base membrane.
[0064] Step 2, synthesis of TA-APTES@PVDF membrane: dissolve 50 mg TA in a beaker containing 25 ml deionized water, add 700 μl APTES, when APTES begins to hydrolyze, put the PVDF base membrane soaked in anhydrous ethanol into it, seal the beaker with a sealing film, and shake in a water bath at 25°C for 40 min. TA and APTES undergo Michael addition reaction to form a TA-APTES micro-nanosphere coating on the PVDF base membrane to prepare a TA-APTES@PVDF membrane.
[0065] Step 3, synthesis of PDMAPAA@TA-APTES@PVDF composite hydrogel membrane: 40 mg FeCl3·6H2O, 10 mg (NH4)2S2O8, and 12 mg MBAA were dissolved in a beaker containing 6 ml deionized water, 50 μl DMAPAA was added, and the prepared TA-APTES@PVDF membrane was placed therein, the beaker was sealed with a sealing film, and the mixture was shaken in a water bath at 25 °C for 2 h. 3+ A dual autocatalytic system was constructed with TA to catalyze the polymerization of DMAPAA to obtain PDMAPAA@TA-APTES@PVDF composite hydrogel membrane.
[0066] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a PDMAPAA@TA-APTES@PVDF composite hydrogel membrane, characterized in that: Here are the steps: Step 1: Preparation of PVDF base membrane: The hydrophobic PVDF membrane is completely infiltrated with anhydrous ethanol to obtain a PVDF base membrane. Step 2: Preparation of TA-APTES@PVDF membrane: TA and APTES undergo Michael addition reaction to form a TA-APTES micro-nanosphere coating on the PVDF base membrane to prepare a TA-APTES@PVDF membrane. Step 3: Preparation of PDMAPAA@TA-APTES@PVDF composite hydrogel membrane: Application of Fe 3+ A dual autocatalytic system was constructed with tannic acid (TA), which reacted at room temperature to initiate the polymerization of dimethylaminopropylacrylamide (DMAPAA) on the surface of the prepared TA-APTES@PVDF membrane to obtain the PDMAPAA@TA-APTES@PVDF composite hydrogel membrane.
2. The method for preparing a PDMAPAA@TA-APTES@PVDF composite hydrogel membrane according to claim 1, characterized in that: In step 1, the commercially available hydrophobic PVDF membrane is completely soaked with anhydrous ethanol and then taken out for the next reaction.
3. The method for preparing a PDMAPAA@TA-APTES@PVDF composite hydrogel membrane according to claim 1, characterized in that: In step 2, the ratio of TA to APTES is 1:2; the reaction conditions are shaking in a water bath at 25° C.; and the reaction time is 30 to 50 min.
4. The method for preparing a PDMAPAA@TA-APTES@PVDF composite hydrogel membrane according to claim 1, characterized in that: In step 3, the reaction conditions are shaking in a water bath at 25°C; the reaction time is 2h, Fe 3+ 50 to 70 mg.
5. A PDMAPAA@TA-APTES@PVDF composite hydrogel membrane, characterized in that: The invention comprises a PVDF membrane, wherein the PVDF membrane is provided with a TA-APTES micro-nanosphere coating and PDMAPAA.
6. The PDMAPAA@TA-APTES@PVDF composite hydrogel membrane according to claim 5, characterized in that The PDMAPAA@TA-APTES@PVDF composite hydrogel membrane is prepared by the method as described in any one of claims 1 to 4.
7. Use of the PDMAPAA@TA-APTES@PVDF composite hydrogel membrane of claim 5 or 6 for separation of oil-water emulsions.
Citation Information
Patent Citations
Preparation method and application of ferri-tannic acid compound modified PVDF film
CN107138055A
Method for preparing polyamide-amine gel composite membrane based on click chemistry and application of polyamide-amine gel composite membrane
CN114031803A
Method for modifying inner wall of straight-through hole membrane channel by using metal-polyphenol
CN114588787A
Preparation method and application of TCPP-coated HPAMAM-coated PA / PVDF bifunctional composite membrane
CN114904400A
Method for preparing TA-APTES deposition coating enzyme membrane based on glycerol regulation and control
CN117965520A
Cited By
Photoinduced self-cleaning high-flux high-adhesion oil-water separation membrane and preparation method thereof
CN121198075A